Penambahan Filtrat Tepung Umbi Dahlia (Dahlia variabilis Willd.) sebagai Prebiotik dalam Pembuatan Yoghurt Sinbiotik - Alfaridhi, Khabib Khasan; Lunggani, Arina Tri; Kusdiyantini, Endang (Bioma : Berkala Ilmiah Biologi, 2013)
Yoghurt is a fermented milk product that can provide beneficial effects to the health of consumers. Increasing the quality of yoghurt can be made by combining the benefits of probiotic with prebiotic to produce sinbiotic yoghurt. Inulin is a prebiotic that found in many dahlia tuber (Dahlia variabilis Willd.). Pure inulin were expensive, so the alternative is using dahlia tuber flours filtrate as prebiotic ingredients. This study aimed to examine the addition of Dahlia Tuber Flours Filtrate (DTFF) as a prebiotic in sinbiotic yoghurt making using Lactic Acid Bacteria (LAB) Lactobacillus bulgaricus, Streptococcus termophilus dan Lactobacillus acidopilus as probiotic. This research using Completely Randomized Design (CRD) with 4 concentration treatments DTFF 0%, 3%, 6% and 9% with 3 replications. Observed variables consist of the number of total LAB, lactic acid level, pH and organoleptic attributes (aroma, flavor, consistency and impression). Data the number of total LAB, lactic acid level and pH values ​​were analyzed by ANOVA, continued by Duncan test, while the organoleptic data was analyzed by Mann-Whitney U test with 95% significant level. The results showed that the addition of DTFF significantly affect the increasing of total LAB, lactic acid level, organoleptic assessment and decreasing pH of sinbiotic yoghurt. Sinbiotic yoghurt with 3% of DTFF concentration is most preferred by panelists and required the criteria of Indonesian National Standard (SNI) for yoghurt with enough likely aroma, sour taste/specify and enough thick texture with total LAB 2,4 x 108 CFU/ml, 1.3% lactic acid levels and 4.2. pH. Keywords : prebiotic, probiotic, inulin, dahlia tuber, sinbiotic yoghurt, lactobacillus bulgaricus, streptococcus termophilus, lactobacillus acidopilus